Effect of Reflexology on the Length of Labor: A Systematic Review and Meta- analysis of Clinical Trials - Leila Bagheri; Ashraf Ghiasi; Elaheh Ahmadnia (Mashhad University of Medical Sciences, 2018)
Introduction: Reflexology is a non-pharmacological pain relief method, the effects of which remain unclear on obstetric interventions. This systematic review and meta-analysis aimed to assess the effect of reflexology on the length of labor. Methods: A literature search was performed in databases such as Cochrane, Medline, PubMed, Scopus, Web of Science, Ovid, Google Scholar, SID, MagIran, IranMedex, and Irandoc using various keywords, including foot massage, childbirth, delivery, natural delivery, vaginal delivery, length of labor, length of delivery, massage therapy, reflexology, labor, labour, randomized clinical trial, and reflex, as well as all the possible combinations. All the clinical trials published during 2000-June 2017 were reviewed in the study. The Jadad scale was used to assess the quality of the retrieved articles. Results: Out of 616 articles (Persian and English) and after removing the repetitive and irrelevant contents, six clinical trials were assessed in this systematic review and meta-analysis. The selected studies were conducted in Iran and Egypt. The results of the meta-analysis revealed that reflexology has a positive effect on reducing the length of the first stage of labor (RR: -0.67; 95% CI: -1.09--0.25; df =3; P=0.02). However, it exerts no effects on the length of the second stage (RR: -3.77; 95% CI: -8.18-0.64; df =2; P=0.22) and third stage of labor (RR: -1.94; 95% CI: -3.47--0.41; df=2; P=0.09). Conclusion: According to the results, reflexology could reduce the length of the first stage of labor, while further investigation on adequate sample sizes is required to evaluate its effects on the second and third stage of labor.